Pemetaan Elemen MOOC Berdasarkan Desain Instruksional - El Vionna Laellyn Nurul Fatich; Paulus Insap Santosa; Ridi Ferdiana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
MOOC (Massive Open Online Course) is an innovation in the field of online learning that has been popular since 2012. MOOC users during the COVID-19 pandemic increased dramatically, but the dropout rate for MOOC was also high. One of the things that causes the high dropout rate is the MOOC design. To get a good MOOC design, it is necessary to design an instructional design. Instructional design is a guide in designing instruction or learning stages to facilitate effective learning so that learning objectives can be achieved. Many examples of instructional design have been introduced in previous studies, one of which is "The 7Cs Learning Design Framework". In this research, a mapping of elements that are found in MOOC will be carried out into the category of MOOC features that are closely related because of the similarity of functions and properties with "The 7Cs Learning Design Framework". It is hoped that after this mapping has been carried out, system developers and MOOC instructors can focus more on a good MOOC design so as to maintain MOOC user retention and satisfaction.